2022
DOI: 10.3390/pathogens11030281
|View full text |Cite|
|
Sign up to set email alerts
|

Surveillance for Onchocerciasis-Associated Epilepsy and OV16 IgG4 Testing of Children 6–10 Years Old Should Be Used to Identify Areas Where Onchocerciasis Elimination Programs Need Strengthening

Abstract: To eliminate onchocerciasis-associated morbidity, it is important to identify areas where there is still high ongoing Onchocerca volvulus transmission. Between 2015 and 2021, door-to-door surveys were conducted in onchocerciasis-endemic villages in Cameroon, the Democratic Republic of Congo (DRC), Nigeria, South Sudan, and Tanzania to determine epilepsy prevalence and incidence, type of epilepsy and ivermectin therapeutic coverage. Moreover, children aged between six and 10 years were tested for anti-Onchocerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…A recent study concluded that today, Simulium dentulosum appears to be the main vector of human onchocerciasis in the area, and that Simulium vorax may be a secondary vector [ 42 ]. Ov16 IgG4 antibody positivity, determined with the Ov16 IgG4 Bioline rapid diagnostic test [ 43 , 44 , 45 , 46 ], between 2016 and 2018 was 0% (0/55) among 6-year-old and 7.1% (13/182) among 7–10-year-old children in the Logo Health zone [ 47 ]. In contrast, the Ov16 seroprevalence, determined with the same rapid test in an area in Maridi close to the blackfly breeding site, was 40% among children 3–6 years old and 66.7% among children 7–9 years old [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study concluded that today, Simulium dentulosum appears to be the main vector of human onchocerciasis in the area, and that Simulium vorax may be a secondary vector [ 42 ]. Ov16 IgG4 antibody positivity, determined with the Ov16 IgG4 Bioline rapid diagnostic test [ 43 , 44 , 45 , 46 ], between 2016 and 2018 was 0% (0/55) among 6-year-old and 7.1% (13/182) among 7–10-year-old children in the Logo Health zone [ 47 ]. In contrast, the Ov16 seroprevalence, determined with the same rapid test in an area in Maridi close to the blackfly breeding site, was 40% among children 3–6 years old and 66.7% among children 7–9 years old [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…less than 20% nodule prevalence by REMO). However, the recent change of objective from onchocerciasis control to elimination of transmission requires new epidemiological mapping (known as 'elimination mapping', using OV-16 serology) so that 'Transmission Zones' (TZs) can be properly defined and CDTI can be extended into hypo-endemic areas [24][25][26]. A TZ is defined as "a geographical area where transmission of Onchocerca volvulus occurs by locally breeding vectors and which can be regarded as a natural ecological and epidemiological unit for interventions" [26].…”
Section: Potential Isolation Of the Focusmentioning
confidence: 99%
“…less than 20% nodule prevalence by REMO). However, the recent change of objective from onchocerciasis control to elimination of transmission requires new epidemiological mapping (known as ‘elimination mapping’, using OV-16 serology) so that ‘Transmission Zones’ (TZs) can be properly defined and CDTI can be extended into hypo-endemic areas (WHO, 2016; WHO-OTS, 2018; Dusabimana et al, 2022). A TZ is defined as “ a geographical area where transmission of Onchocerca volvulus occurs by locally breeding vectors and which can be regarded as a natural ecological and epidemiological unit for interventions ” (WHO, 2016).…”
Section: Introductionmentioning
confidence: 99%